NILAI PROGNOSTIK KADAR GULA DARAH KAPILER DAN TEKANAN DARAH TERHADAP KELUARAN STROKE ISKEMIK AKUT - Azwita Effrina Hasibuan, Aida Fithrie, Puji Pinta Omas Sinurat, Darulkutni Nasution (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION RECENTLY EVIDENCE SHOWED THE INFLUENCE OF HYPERGLYCEMIA AND BLOOD PRESSURE IN ACUTE STROKEHIGH BLOOD GLUCOSE LEVEL AND HIGH BLOOD PRESSURE ASSOCIATED WITH INCREASE RISK OF POOR OUTCOME HOWEVER THERE IS NO BLOOD GLUCOSE AND BLOOD PRESSURE TRESHOLD AS A PREDICTOR OF ACUTE ISCHEMIC STROKE OUTCOME